Pengaruh Gratis Ongkir, Flash Sale, Ulasan Konsumen, dan Kepercayaan Konsumen terhadap Keputusan Pembelian di Shopee - Yusuf Yusuf; Rizki Nur Rofilah; Wa Ode Aqilah Tsaniyah Sabrina Arafatputri; Wa Ode Nabila Wardatul Asya; Wa Ode Sitti Asrianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Indonesia's e-commerce market has experienced rapid growth, leading to increasingly intense competition among online marketplaces. To remain competitive, Shopee has introduced a variety of promotional programs while continuing to strengthen consumer trust in order to influence purchasing decisions. Although previous studies have discussed the roles of free shipping, flash sales, consumer reviews, and consumer trust, these factors are generally examined separately, leaving limited conceptual discussion of how they work together. Using a qualitative library research approach, this paper brings together relevant theories and findings from previous studies to explain how these variables are conceptually related. Findings from the reviewed literature indicate that free shipping reduces consumers' perceived transaction costs, while flash sales create urgency that can encourage impulsive buying. Consumer reviews contribute through electronic word-of-mouth (e-WOM), helping potential buyers evaluate products and reduce perceived risk before making a purchase. Consumer trust, viewed through the Ability–Benevolence–Integrity (ABI) model, strengthens the effectiveness of these promotional strategies by increasing confidence in both the platform and its sellers. By bringing these perspectives together, this paper offers an integrated conceptual framework that can serve as a useful reference for future empirical research, particularly studies employing structural equation modeling.